Structure and evolution of electron "zebra stripes" in the inner radiation belt. Issue 5 (10th May 2016) - Liu, Y.; Zong, Q.‐G.; Zhou, X.‐Z.; Foster, J. C.; Rankin, R.
Abstract: "Zebra stripes" are newly found energetic electron energy‐spatial (L shell) distributed structure with an energy between tens to a few hundreds keV in the inner radiation belt. Using high‐quality measurements of electron fluxes from Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) on board the twin Van Allen Probes, we carry out case and statistical studies from April 2013 to April 2014 to study the structural and evolutionary characteristics of zebra stripes below L = 3. It is revealed that the zebra stripes can be transformed into evenly spaced patterns in the electron drift frequency coordinate: the detrended logarithmic fluxes in each L shell region can be well described by sinusoidal functions of drift frequency. The "wave number" of this sinusoidal function, which corresponds to the reciprocal of the gap between two adjacent peaks in the drift frequency coordinate, increases in proportion to real time. Further, these structural and evolutionary characteristics of zebra stripes can be reproduced by an analytic model of the evolution of the particle distribution under a single monochromatic or static azimuthal electric field. It is shown that the essential ingredient for the formation of multiple zebra stripes is the periodic drift of particles. The amplitude of the zebra stripes shows a good positive correlation with K p index, which indicates that the generation mechanism of zebra stripes should be related to geomagnetic activities. Key Points: Zebra stripes are evenly spaced patterns in electron drift coordinate Zebra stripes evolves in proportion to real time Zebra stripes are produced by electron motion under static/single monochromatic electric field